Birth outcomes of children born to women with rheumatoid arthritis - Pósfai, Éva; Bánhidy, Ferenc; Urbán, Róbert; Czeizel, Andrew E (Central European Journal of Public Health, 2015)
AIM: The aim of the study was to estimate the possible risk of adverse birth outcomes of children born to mothers with rheumatoid arthritis (RA). METHODS: The dataset of large population-based Hungarian Case-Control Surveillance System of Congenital Abnormalities from 1980-1996 was evaluated including 22,843 cases with congenital abnormalities and 38,151 matched controls without any defect. RESULTS: 36 cases (0.16%) had mothers with RA, while 68 controls (0.18%) were born to mothers without RA (OR=0.9, 95% CI=0.3-1.6). A higher risk for congenital abnormalities in the offspring of pregnant women with RA was not found. In fact there was a larger mean birth weight in the newborns without any defect of mothers with RA and it was associated with a somewhat lower rate of low birth weight. CONCLUSIONS: RA seems to have a beneficial effect not only for pregnant women but for their foetuses as well.
Keywords: vrozené vady; dospělí; Arthritis, Rheumatoid; Female; revmatoidní artritida; novorozenec; Adult; ženské pohlaví; lidé; Infant, Newborn; surveillance populace; Pregnancy Outcome; těhotenství; Congenital Abnormalities; studie případů a kontrol; Case-Control Studies; Population Surveillance; výsledek těhotenství; Hungary; Maďarsko; Pregnancy; Humans